Functional properties of Australian blue lupin (Lupinus angustifolius) protein and biological activities of protein hydrolysates. Issue 1 (9th December 2020) - Kamran, Fozia; Phillips, Michael; Reddy, Narsimha
Abstract: Lupin is an undervalued legume despite its high protein content with known health benefits. In this research, Australian blue lupin protein was isolated and hydrolysed enzymatically to produce bioactive peptides with a view to assess their potential for nutraceutical and therapeutic applications. Pepsin, pancreatin and flavourzyme were used to enzymatically hydrolyse blue lupin protein, and the hydrolysates were subjected to molecular weight cut‐off (MWCO) fractionation. Measurement of biological activities led to the identification of angiotensin converting enzyme (ACE) inhibitory fractions in the molecular weight range of 2–3 and 3–5 kDa. For the most active fractions in this range, the ACE inhibitory activities were very significant with IC50 values from 450 to 600 μg/ml. Blue lupin protein‐derived MWCO fractions were significantly active against Gram‐positive bacteria and only a little inhibition was observed against Gram‐negative bacteria. Pancreatin hydrolysed fractions showed the best antimicrobial activities with several fractions exhibiting ≥85% inhibition against Bacillus cereus and Staphylococcus aureus . These properties reveal the potential of lupin protein hydrolysates for developing antihypertensive and host defence agents. In order to demonstrate the potential of isolated blue lupin protein in food industry, functional properties including water and oil absorption capacity, gelling properties, solubility and emulsifying properties were evaluated and found to be extremely suitable for developing functional foods with enhanced health benefits.